How Ecological Disturbances May Influence Mountain Quail in the Pacific Northwest - Michael D. Pope; Patricia E. Heekin (National Quail Symposium Proceedings, 2017)
Mountain quail (Oreortyx pictus) populations have declined throughout the Intermountain Region of the Pacific Northwest. The decline of mountain quail is most likely related to the loss of habitat. We suggest that disturbance may play a critical role in providing the structure, composition, and density of vegetation needed to sustain mountain quail populations. Conversely, lack of disturbance (fire suppression) may result in conditions unsuitable for mountain quail. We examined the historic role and ecological influences of fire on vegetation in the Intermountain Region, and how the elimination of fire as a successional determinant may have facilitated the decline of mountain quail. Limited cattle grazing, prescribed burning, and silvicultural practices may provide alternatives to natural fire for establishing and/or maintaining mountain quail habitat.